2018
DOI: 10.21273/hortsci13469-18
|View full text |Cite
|
Sign up to set email alerts
|

Continuous Irradiation with Alternating Red and Blue Light Enhances Plant Growth While Keeping Nutritional Quality in Lettuce

Abstract: Plant factories with artificial lighting have been developed to improve food production, functional ingredients, and profitability. Intensive research has been performed to elucidate the effects of light intensity and wavelength on plant growth and nutritional quality with the use of light-emitting diodes (LEDs). In particular, the effects of monochromatic red, blue, or simultaneous red + blue light have been studied because these wavelengths are predominantly used for photosynthesis. We examined the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
55
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(60 citation statements)
references
References 47 publications
(55 reference statements)
4
55
1
Order By: Relevance
“…During the initial stages of our experiment (late November–early December), the natural light intensity was low, and the natural photoperiod is short, thus, supplemental lighting had the largest effect. Similar to results in Ohtake et al (2018) using lettuce, during this period, plants grown under CL had a larger leaf area and taller stem height than plants grown under 12 h lighting. Since day-time NCER are similar between the two treatments, it is likely that elevated NCER between 18:00–06:00 from the CL treatment allocated more carbon for vegetative growth ( Figure 4 ).…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…During the initial stages of our experiment (late November–early December), the natural light intensity was low, and the natural photoperiod is short, thus, supplemental lighting had the largest effect. Similar to results in Ohtake et al (2018) using lettuce, during this period, plants grown under CL had a larger leaf area and taller stem height than plants grown under 12 h lighting. Since day-time NCER are similar between the two treatments, it is likely that elevated NCER between 18:00–06:00 from the CL treatment allocated more carbon for vegetative growth ( Figure 4 ).…”
Section: Discussionsupporting
confidence: 79%
“…In our study, wavelength specific LEDs were utilized to create an alternating spectrum CL regime which produced injury-free tomato plants. The utilization of LEDs to produce an alternating spectrum during CL has been previously documented in lettuce (Ohtake et al, 2018). In this study using lettuce, an alternating CL spectrum with red light during the day (12 h) and blue light during the night (12 h) produced the highest dry weight and leaf area compared to a CL with a constant red/blue spectrum and a CL provided by fluorescent lights (Ohtake et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2), and the largest leaves were observed under the 1-h treatment; larger leaves capture more light energy to increase the net photosynthetic rate, resulting in the highest biomass of two-leaf-color pak choi under the 1-h treatment (Table 2). According to previous research, compared with simultaneous irradiation with red and blue light, alternating red and blue light promotes the growth of lettuce, especially at 22 to 31 d (Ohtake et al, 2018), suggesting a significant effect of alternating irradiation on plants in the later cultivation period. In addition, it was shown that with the exception of consistent irradiation with red and blue light, the fresh and dry weights of lettuce under alternating red and blue light exposure were highest with an interval of 1 h vs. 2, 4, and 8 h (Chen et al, 2019), which was consistent with the results of the present study.…”
Section: Plant Typementioning
confidence: 76%
“…The length of the petiole and the stem length of lettuce reached their maximum levels under intermittent red and blue light exposure with intervals of 6 and 1 h (Shimokawa et al, 2014). Red and blue light promote leaf expansion, and alternating red and blue light exposure contributes to elongating the leaves of lettuce (Ohtake et al, 2018). The results showed that the leaves of both cultivars of pak choi were larger under supplemental alternating red and blue light than they were at 0 h (Fig.…”
Section: Plant Typementioning
confidence: 84%